Sovereign risk: A macro-financial perspective - Udaibir S. Das; Maria A. Oliva; Takahiro Tsuda (Asian Development Bank Institute (ADBI), 2012)
We examine some of the macro-financial dimensions of sovereign risk and propose a conceptual framework that captures risks other than just the default risk. Morphed under a multi-dimensional notion of sovereign risk, we argue that the existing empirical methodologies to measure sovereign risk cover only partial aspects of sovereign risk and fail to capture its macro-financial dimensions. We highlight a menu of tools that could be used to tackle the broader notion of sovereign risk, and suggest that authorities should actively use them to manage the macro-financial dimensions of sovereign risk before those risks feed into the real economy.
Keywords: F30; F34; E43; 330; sovereign risk; default risk; macro-financial dimensions; Länderrisiko; Spillover-Effekt; Finanzkrise; Makroökonomischer Einfluss; Schuldenmanagement; Welt